Mencari Kartika [videorecordings] a documentary film. - Kaprawi, Norhayati (Malaysia Lensa Srikandi, 2010)
This documentary film explores the Muslim's perception of "justice" in the context of Malaysia that is lauded for its moderm, progressive, multi-racial image. Kartika herself has endorsed the film, saying that it offers viewers a larger truth about her actions and statements after she has sentenced.
A 30-minute version of the film, co-directed by Norhayati Kaprawi and Ucu Agustin, was screened at the V Women Film Festival in Jakarta in March 2010. Screenings of the 40 min verion held by NGO, art spaces and universities in Malaysi and abroad were met with enthusiasm by the media and the public
Keywords: Women -- Malaysia; Muslim Women